Community Empowerment in Postpartum Mothers' Behavior Regarding Baby Massage in Ladang Bambu Village, Medan Tuntungan District - Karsana, Karsana; Violent, Violent (Benih : Journal of Midwifery, 2023)
Baby massage is one of the complementary therapies and self-care for postpartum mothers. There are many benefits of baby massage, one of which is to improve the quality of baby's sleep. Babies with good quality sleep can help optimize their growth and development. This community service aims to train and assist postpartum mothers who have babies in improving their sleep quality through baby massage. The purpose of this community service is to determine the ability and understanding of the community or postpartum mothers regarding performing massage on the duration of sleep of babies aged 3-6 months. Based on the results of a survey conducted on November 22, 2023 in Ladang Bambu Village, Medan Tuntungan District. The method used in empowerment activities is to provide health education on performing massage on the duration of sleep of babies aged 3-6 months, giving rewards to mothers. The results achieved after participating in community empowerment and discussion in Ladang Bambu Village, Medan Tuntungan District to determine the improvement in the ability and behavior of mothers in massaging babies aged 3-6 months.